A Randomized Controlled Trial Examination of a Remote Parenting Intervention: Engagement and Effects on Parenting Behavior and Child Abuse Potential. (November 2017) - Baggett, Kathleen; Davis, Betsy; Feil, Edward; Sheeber, Lisa; Landry, Susan; Leve, Craig; Johnson, Ursula
Technology advances increasingly allow for access to remotely delivered interventions designed to promote early parenting practices that protect against child maltreatment. Among low-income families, at somewhat elevated risk for child maltreatment, there is some evidence that parents do engage in and benefit from remote-coaching interventions. However, little is known about the effectiveness of such programs to engage and benefit families at high risk for child maltreatment due to multiple stressors associated with poverty. To address this limitation, we examined engagement and outcomes among mothers at heightened risk for child abuse, who were enrolled in a randomized controlled, intent-to-treat trial of an Internet adaptation of an evidence-based infant parenting intervention. We found that engagement patterns were similar between higher and lower risk groups. Moreover, an intervention dose by condition effect was found for increased positive parent behavior and reduced child abuse potential.